Determination of Inflation Sistercity in Riau Province by Using K-Means Clustering Method - Kesuma, M Nata; Yufa, Pedro Rahmat; Hariyanti, Fitri (Politeknik Statistika STIS, 2025)
At the present time, the government is placing a significant emphasis on the regulation of inflationary pressures. The government's approach is multifaceted, ranging from the Minister of Home Affairs' direct leadership of coordination meetings on Monday mornings to providing fiscal incentives for regions that can control inflation and removing local government officials who cannot. However, note that BPS-Statistics Indonesia (BPS) does not calculate inflation in all Indonesian regencies and cities. The calculation of inflation only includes four out of the 12 regencies/cities in Riau Province. Therefore, we must establish an inflation sister city to allow regencies/cities not included in BPS's calculations to independently calculate the inflation rate. This study is pioneering in its analysis of Sister City Inflation in Riau Province. The k-means cluster analysis indicates that the city of Pekanbaru and the city of Tembilahan form distinct clusters, with no regencies or cities within their respective clusters that are associated with either of the two cities. Subsequently, the Dumai cluster forms a cluster with Bengkalis, Siak, and Pelalawan. Conversely, Kampar Regency formed a cluster with Kuantan Singingi, Indragiri Hilir, Indragiri Hulu, Rokan Hulu, Rokan Hilir, and the Meranti Islands. Consequently, regions that are not included in the inflation calculation may utilize the data from the cost of living survey in inflation regencies/cities within the same cluster to perform their calculations. Furthermore, if the local government requires the inflation rate as a reference for determining the regional minimum wage, it may employ it from the sister cities that have been established.